Vtoroi s"ezd KPRSFSR . Vtoroi s"ezd KPRSFSR . Second Congress of the Communist Party of the Russian Federation . Второй съезд КП РСФСР - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of the political and economic situation on the territory of the former USSR, and of the task of strengthening peace, security, and détente. Featured in the program: Osadchii, Ivan (Member of the Central Election Commission of the Communist Party of the Russian Federation) Обсуждение политической и экономической ситуации на территории бывшего Советского Союза, а также задачи упрочнения мира, безопасности и разрядки. В программе участвуют: Осадчий, Иван (Член ЦИК Компартии РФ)